Food Away From Home and Self-Perceived Gastrointestinal Health - Chen, Jyh-Jou; Tsai, Li-Yun; Tsai, Jung-Mei; Hsu, Chen-Yuan (Frontiers in Nutrition, 2021)
Dietary behavior is a critical lifestyle factor affecting health. This study aimed to investigate food away from home (FAFH) and its effect on gastrointestinal (GI) health. A questionnaire-based survey was conducted with 300 participants at a hospital in Liouying, Taiwan. The survey collected demographic information and data on FAFH and GI health. The association of GI health with FAFH consumption behavior was significant (t-test, p < 0.05). Bodyweight status was associated with age (F = 5.01, p = 0.01), dietary situation (F = 1.96, p = 0.04), number of meals (F = 1.85, p = 0.03), dietary preferences (F = 2.84, p = 0), reasons for FAFH (F = 1.86, p = 0.02), FAFH types (F = 2.01, p = 0), and outcomes associated with FAFH (F = 2.51, p = 0). Gastrointestinal condition was associated with the number of meals (F = 2.55, p = 0), the level of activity after meals (F = 2.16, p = 0.02), and FAFH type (F = 1.48, p = 0.04). The results indicated that the participants aged 20–40 years had more problems related to their self-perceived body weight status than those aged 41–50 years. The results of this study clarify the FAFH among people in Taiwan and the effects on GI health and may serve as a reference for relevant behavioral research in food and health studies.